News. (Computer (00189162), 2015)
Topics include hackers attacking the Internet naming authority, a new Bluetooth version offering online connectivity and showing promise for the Internet of Things, companies looking for ways to enable mobile apps to communicate with one another, the US planning the world's most powerful supercomputer, a set of prosthetic arms that users can control with their thoughts, hackers hitting a German steel factory and a South Korean nuclear power plant, NASA using apes as the model for a disaster-response robot, Sony inventing a system that converts regular glasses into smart spectacles, researchers finding a critical flaw in an important cloud technology, a new approach letting cellular towers function like inexpensive radar, and a program teaching California prisoners to program.